Biff, Chip and Kipper stories. Group/guided reading notes Stage 9 - Howell, Gill (Oxford University Press Oxford, 2011)
The Level 9 Biff, Chip and Kipper Stories, written by Roderick Hunt and illustrated by Alex Brychta, provide a rich story context to help develop language comprehension and decoding skills. Stories and More Stories A continue to provide a mix of fantasy settings and familiar situations. More complex sentences with conceptually more challenging storylines develop stamina, ensuring that readers will be able to progress to more demanding texts with confidence. Books contain inside cover notes to support children in their reading